GEOMETRIC QUALITY ANALYSIS OF THE GNSS NETWORK LOCATION OF UFU - SANTA MONICA CAMPUS - Araújo Silva, Lorena; Lígia Chuerubim, Maria; Carolina Gonzaga Pires, Ana; Guedes Gomes, Plínia (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
In order to suit the development of researches, practical classes and others outreach activities, it was verified the importance of improve the quality of the network Global Navigation Satellite Systems (GNSS) location of Federal University of Uberlândia (UFU), Santa Monica campus. The GNSS network of the university is the passive network that was implanted six years ago, with approximately 19 stations. In the following years, new densification was performed by adding four stations: CIV01, CIV02, CIV03 and CIV06. However, many stations were uprooted and/or relocated because of the campus ' expansion and the servers and community's lack of information.